Anxiety states among Hellenic emergency department and intensive care nurses: a comparative study - Kalafati, Maria; Stathopoulou, Hariklia; Papathanassoglou, Elizabeth; Karanikola, Maria (My University, 2009)
Purpose: The aim of the study was a) to examine the metric properties of the Hellenic version of Hamilton?s Anxiety scale for nurses, and b) to explore anxiety states among Hellenic emergency (ER) and intensive care (ICU) nurses, as well as potential differences between the two populations. Methods: A correlational cross- sectional design was employed. A random sample of 131 emergency and 136 intensive care nurses completed the Hamilton?s scale for the assessment of anxiety states. The psychometric properties of the Hamilton scale were tested and descriptive and inferential statistics were explored. Results: Internal consistency (Cronbach?s alpha = 0.864) and test-retest (tau= 0.934, p<0,0001) reliability of the Hamilton?s scale were high. The construct validity of the scale was tested by exploratory factor analysis (Barlett test x2 =4217.39, p<0.0001/ KMO =0.803) with Varimax rotation (eigenvalue>1) which resulted in 13 factors that accounted for the 60,93% of the variance. These findings confirmed Halmilton?s analysis. Mild anxiety states were measured for both ER (1.019 ± 0.64) and ICU (0.674 ± 0.34) nurses. ER nurses exhibited a statistically significant higher level of anxiety (Mann-Whitney U, p<0.0001). Statistically significant differences (Mann-Whitney U, 0.01<p<0.0001) were also detected between ER and ICU nurses regarding sleep disturbances, depression symptoms, muscular symptoms and symptoms from autonomic nervous system. A statistically significant mild correlation was observed between preoccupation and anxiety states for both ER (Kendall?s tau=0.162, p=0.013) and ICU (Kendall?s tau=0.131, p=0.03) nurses. Conclusion: Based on these results, hospital administrators need to be aware of the extent of workplace stress and subsequent anxiety symptoms in emergency and intensive care nurses. New stress reduction policies may need to be implemented in order to prevent psychiatric morbidity, as well as job dissatisfaction and resignations.
Keywords: Anxiety; Burnout; Hamilton's Anxiety; Intensive care